EMAR monitoring system applied to the thickness reduction of carbon steel in a corrosive environment. Issue 5 (21st January 2022) - Diguet, Gildas; Miyauchi, Hina; Takeda, Sho; Uchimoto, Tetsuya; Mary, Nicolas; Takagi, Toshiyuki; Abe, Hiroshi
Abstract: Nondestructive techniques are one viable solution to monitor structure health in material science. Among available solutions, the electromagnetic acoustic transducer is a contactless method allowing access to the thickness of a material. This study aims to apply and validate its measurement accuracy on a carbon steel plate submitted to corrosion in an acid solution. Steel thickness reduction is estimated from either electrochemical or electromagnetic acoustic resonance (EMAR) tests along the immersion period. These values are then compared to ex situ profilometry measurements. On the one hand, the results show the underestimation of the material loss from the electrochemical measurements because of the reactivity modification induced by the precipitation of an oxide layer. On the other hand, EMAR and profilometry measurements are in good agreement indicating that EMAR provides reliable information on material thickness reduction. Abstract : A metal steel coupon has its thickness reduced by corrosive solution in an electrochemical cell. At the same time, an electromagnetic acoustic resonance (EMAR) is used to measure the thickness with the time of corrosion. Change of thickness is evaluated and compared using Faraday's law, the EMAR, and direct surface profile measurements.